Desenvolvimento de protótipos de testes imunocromatográficos para detecção de anticorpos específicos de leptospiras patogênicas em ratos e cães - Souza, Dienny Rodrigues de (2018)
Leptospirosis is a zoonosis caused by pathogenic spirochetes belonging to the genus Leptospira. The disease may progress to acute renal failure (Weil's Syndrome) and severe pulmonary haemorrhagic syndrome (SPHS), with a mortality rate of > 50%. The highest incidence of the disease occurs among the poorer populations and is associated with the lack of basic sanitation that gets worse during periods of heavy rainfall and flooding. Rodents and dogs are the main sources of transmission of the disease. Therefore, the identification of infected animals is essential towards eliminating reservoir hosts such as dogs and rodents. Therefore, means allowing the identification of leptospira infection in dogs and rodents is essential to permit control actions, decreasing the infection rate in the environment and consequently helping to prevent disease in humans. The objective of this study was to develop prototypes of lateral flow immunochromatographic tests to aid in the diagnosis and control of leptospirosis. The design used in the prototypes was based on a lateral flow immunochromatographic test for direct detection of specific antibodies using a recombinant antigen, known as rLigBrep, attached to the nitrocellulose membrane test line. As an antigen/antibody binding marker, polyvalent antibodies were conjugated to 40 nm colloidal gold, murine anti-mouse immunoglobulin for the murine, anti-canine (Rockland) and anti-canine IgG (Jackson) for canine prototypes. The canine prototypes were tested with 10 positive samples and 10 negative samples previously confirmed by the MAT and ELISA for canine leptospirosis. The staining intensity was recorded on a scale of 0 to 3. Low concentrations of rLigBrep antigen resulted in weak staining intensity. The results of the murine prototype provided the basic specifications to developed the canine prototypes. In the first canine prototype using Rockland conjugate, 5/10 positive samples presented staining intensity of 1. In the canine prototype using Jackson conjugate, 9/10 positive samples presented staining intensity variation of 1 to 3. The results of negative samples 8/10 presented a tenuous staining intensity on the test line, indicating the necessity to reduce the concentration of antigen and/or conjugate on the test. The studied prototypes were not evaluated to determine sensibility and specificity as they didn’t present similar results obtained on ELISA and MAT. Therefore, it has not been defined if the rLigBrep protein can be utilized in the development of a rapid immunochromatography test for the diagnosis of canine leptospirosis and as a marker of infection in rodents.